The Politics of Survival : Peirce, Affectivity, and Social Criticism - Trout, Lara (Book collections on Project MUSE., 2010)
How can sincere, well-meaning people unintentionally perpetuate discrimination based on race, sex, sexuality, or other socio-political factors? To address this question, Lara Trout engages a neglected dimension of Charles S. Peirce's philosophy - human embodiment - in order to highlight the compatibility between Peirce's ideas and contemporary work in social criticism. This compatibility, which has been neglected in both Peircean and social criticism scholarship, emerges when the body is fore-grounded among the affective dimensions of Peirce's philosophy (including feeling, emotion, belief, do.